COMPETENCE APPROACH - AS A MEANS OF DEVELOPMENT MODERN ECONOMIC EDUCATION - M.H. Viyevska (Academy of Cognitive and Natural Sciences, 2007)
In the article, the essence o f notion is considered "competence", value of competence of specialists economic type, new approaches in relation to forming of competence of specialists in higher educational establishments.